THE VACUUM ENERGY OF QED WITH 4-FERMION INTERACTION - Montero, J. C.; Natale, A. A.; PLEITEZ, V; Sobrinho, JAS (Springer, 1992)
We consider quantum electrodynamics in the quenched approximation including a four-fermion interaction with coupling constant g. The effective potential at stationary points is computed as a function of the coupling constants alpha and g and an ultraviolet cutoff LAMBDA, showing a minimum of energy in the (alpha, g) plane for alpha = alpha(c) = pi/3 and g = infinity. When we go to the continuum limit (LAMBDA --> infinity), keeping finite the dynamical mass, the minimum of energy moves to (alpha = 0, g = 1), which correspond to a point where the theory is trivial.